A85 LIKELIHOOD OF ENDOSCOPY CANCELLATION BASED ON VANCOMYCIN-RESISTANT ENTEROCOCCI (VRE) COLONIZATION STATUS AND INFECTION CONTROL PRACTICES. (21st February 2022) - Lee, J G; Ou, G
Abstract: Background: "Terminal cleaning" is a practice of rigorous cleaning of endoscopy suite following endoscopies for patients colonized with vancomycin-resistant enterocci (VRE) with the intention of reducing VRE transmission. Such practice entails double-wiping all surfaces including the floor with disinfectants before a non-VRE patient can use the endoscopy room. While intuitive, such time-consuming practice is not supported by evidence and may have unintended negative impact on patient access to timely endoscopic evaluation. Aims: To determine whether terminal cleaning of endoscopy suite for VRE-colonized patients has any negative impact on inpatient access to timely endoscopic evaluation. Methods: As part of a quality improvement study, inpatient endoscopy data was gathered over a 3-month period between February 2021 and April 2021 at a tertiary centre. EUS, ERCP, and travel cases outside of the endoscopy suite were excluded. The cancellation rates were compared between VRE-colonized patients and non-VRE patients using the Fisher's exact test. P value of <0.05 was considered statistically significant. Results: A total of 262 inpatient endoscopic procedures were scheduled and included in the study. Sixty-six (25.2%) of inpatient procedures were cancelled during this period (Table 1). A total of 24 procedures were scheduled for VRE patients, 9 of which were cancelled because of insufficient operating time and two due to concurrent carbapenamase-producing organism carriage and poor bowel preparation. In the non-VRE group, 55 (23.3%) procedures were cancelled for various reasons (Table 1). In subgroup analysis where cancellations related to COVID-19 (n=14) were omitted, VRE patients had a significantly higher rate of procedure cancellations compared to non-VRE patients (42.3% vs. 18.5%; p<0.01). Conclusions: The overall endoscopy cancellation rate for VRE-colonized patients was higher than those who were non-VRE-colonized. We propose that this is likely secondary to the delays from unnecessary terminal cleans imposed for VRE-colonized patients and await for post-intervention data. Funding Agencies: None